Nasal high flow oxygen therapy during acute admissions or periods of worsening symptoms. Issue 4 (December 2021) - Munsif, Maitri; McDonald, Christine; Goh, Nicole; Smallwood, Natasha
Abstract : Purpose of review: Nasal high flow therapy (NHF) is increasingly used in acute care settings. In this review, we consider recent advances in the utilization of NHF in chronic obstructive pulmonary disease (COPD), terminal cancer and symptom management. Considerations around NHF use during the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic are also discussed. Recent findings: NHF enables humidification and high flows to be provided together with titrated, supplemental oxygen therapy. Compared to conventional oxygen therapy, NHF improves respiratory physiology by reducing workload, enhancing muco-ciliary clearance and improving dead space washout. Some studies suggest that early use of NHF in people being cared for in the emergency department leads to lower rates of invasive ventilation and noninvasive ventilation. There is also emerging evidence for NHF use in people with COPD and chronic respiratory failure, and in palliative care. NHF is comfortable, well-tolerated and safe for use in the management of breathlessness in people with cancer. NHF can be delivered by face mask to patients with SARS-CoV-2 infection, to ease the burden on critical care resources. Summary: The evidence base for NHF is rapidly growing and offers promise in relieving troublesome symptoms and for people receiving palliative care.